Anodically fabricated TiO2–SnO2 nanotubes and their application in lithium ion batteries. Issue 15 (24th March 2016) - Madian, M.; Klose, M.; Jaumann, T.; Gebert, A.; Oswald, S.; Ismail, N.; Eychmüller, A.; Eckert, J.; Giebeler, L.
Abstract : Developing novel electrode materials is a substantial issue to improve the performance of lithium ion batteries. Abstract : Developing novel electrode materials is a substantial issue to improve the performance of lithium ion batteries. In the present study, single phase Ti–Sn alloys with different Sn contents of 1 to 10 at% were used to fabricate Ti–Sn–O nanotubes via a straight-forward anodic oxidation step in an ethylene glycol-based solution containing NH4 F. Various characterization tools such as SEM, EDXS, TEM, XPS and Raman spectroscopy were used to characterize the grown nanotube films. Our results reveal the successful formation of mixed TiO2 /SnO2 nanotubes in the applied voltage range of 10–40 V. The as-formed nanotubes are amorphous and their dimensions are precisely controlled by tuning the formation voltage which turns Ti–Sn–O nanotubes into highly attractive materials for various applications. As an example, the Ti–Sn–O nanotubes offer promising properties as anode materials in lithium ion batteries. The electrochemical performance of the grown nanotubes was evaluated against a Li/Li + electrode at a current density of 504 μA cm −2 . The results demonstrate that TiO2 /SnO2 nanotubes prepared at 40 V on a TiSn1 alloy substrate display an average 1.4 fold increase in areal capacity with excellent cycling stability over more than 400 cycles compared to the pure TiO2 nanotubes fabricated and tested under identical conditions. This electrode was tested at current densities of 50, 100, 252, 504 and 1008 μA cm −2 exhibiting average capacities of 780, 660, 490, and 405 μA cm −2 ( i.e. 410, 345, 305 and 212 mA h g −1 ), respectively. The remarkably improved electrochemical performance is attributed to enhanced lithium ion diffusion which originates from the presence of SnO2 nanotubes and the high surface area of the mixed oxide tubes. The TiO2 /SnO2 electrodes retain their original tubular structure after electrochemical cycling with only slight changes in their morphology.